2014
DOI: 10.4269/ajtmh.14-0126
|View full text |Cite
|
Sign up to set email alerts
|

Cluster Randomized Trial of Text Message Reminders to Retail Staff in Tanzanian Drug Shops Dispensing Artemether-Lumefantrine: Effect on Dispenser Knowledge and Patient Adherence

Abstract: Artemisinin combination therapies are available in private outlets, but patient adherence might be compromised by poor advice from dispensers. In this cluster randomized trial in drug shops in Tanzania, 42 of 82 selected shops were randomized to receive text message reminders about what advice to provide when dispensing artemether-lumefantrine (AL). Eligible patients purchasing AL at shops in both arms were followed up at home and questioned about each dose taken. Dispensers were interviewed regarding knowledg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(42 citation statements)
references
References 37 publications
3
37
2
Order By: Relevance
“…Seven articles studied communication between a health worker and patients, with the emphasis on improving health worker efficiency by saving travel time and gaining work time 11,12,22,2528 . Texts focused on increasing access to skilled attendants at birth 26 , patient medication adherence 22,25 , appointment reminders 22,26 , and tracking patients 11,12 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven articles studied communication between a health worker and patients, with the emphasis on improving health worker efficiency by saving travel time and gaining work time 11,12,22,2528 . Texts focused on increasing access to skilled attendants at birth 26 , patient medication adherence 22,25 , appointment reminders 22,26 , and tracking patients 11,12 .…”
Section: Resultsmentioning
confidence: 99%
“…Texts focused on increasing access to skilled attendants at birth 26 , patient medication adherence 22,25 , appointment reminders 22,26 , and tracking patients 11,12 . There was greater improvement in urban areas as compared to rural areas in health outcomes for patients after a text message reminder intervention 26 , but this was not the case in a program directed at pharmacists to help their patients increase adherence through text 25 . Fuel savings and travel time-savings were substantial for both health worker and patient 22,27 , and it became easier to enroll patients into programs 22 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors identified as leading to the programs' failure included limited phone access, privacy concerns, phone maintenance, and text message content. [30][31][32] A recent literature review of text messaging's effect on health concluded that most studies were not carried out systematically. 33 Using a cluster RCT design, we aimed to test whether text message reminders sent to caregivers' mobile devices would improve the effectiveness of a home micronutrient fortification program.…”
mentioning
confidence: 98%
“…[13][14][15][16] A variety of interventions have been tested to increase adherence rates to ACTs with moderate degrees of success across different contexts. [17][18][19][20] We hypothesized that an important driver of nonadherence is diagnostic uncertainty, as few patients with suspected malaria receive diagnostic confirmation of malaria via blood test. 1,21,22 At the time of the study, malaria diagnostic testing was available in 35% of public health facilities in Uganda (4% had rapid diagnostic tests [RDTs]), 47% of private facilities, and 4% of private drug shops.…”
Section: Introductionmentioning
confidence: 99%